Clinicopathology and Recurrence Analysis of 44 Jaw Aneurysmal Bone Cyst Cases: A Literature Review - Liu, Yu (Front Surg, 2021)
In the past half-century, considerable attention has been paid to oral and maxillofacial skeletal cyst, however, aneurysmal bone cyst (ABC), unlike other common bone diseases, still contours numerous unanswered questions in terms of classification, etiology and pathological mechanism. The purpose of this article was to evaluate the proportion of primary ABC and secondary ABC, and to assess the recurrence of ABC and related factors. A methodical search of Embase, MEDLINE, Cochrane Library, Web of Science was conducted for well-documented jaw aneurysmal bone cyst (JABC) cases. One hundred thirty-one articles were identified after database searching and 31 of them were included in our study for further research with 44 JABC cases. All the articles were analyzed by two separate authors. About 25% of the reported jaw aneurysmal bone cyst was secondary. Both the pathological classification and surgical treatment had a significant influence on recurrence rate (P = 0.0082, P = 0.0022), while patients' age or radiographic features rarely affected prognosis. Jaw aneurysmal bone cysts can present variable clinical and histological presentations. Recurrence may be attributed to omittance of underlying potential blood supply or conservative surgical protocol.